Bioelectrical impedance analysis of fat in the body composition influenced by Ogawa MasterDrive 4D / Serena Low Woan Ching - Serena Low, Woan Ching (2019)
Ogawa MasterDrive 4D is a state-of the art massage chair that was designed to bring relaxation to your home. The chair was equipped with heat function that allow the user to experience warm hand-like massages that claimed to increase the metabolic rate of the user and subsequently reduce body fat. Bioelectrical Impedance Analysis (BIA) is a technique that is used to estimate the body composition of the human body. It is well known for its noninvasive approach, simplicity, convenience, affordable price and it is able to obtain instant results of your body immediately without technical supervision. The objective of this study is to test the claim from Ogawa by using two BIA devices to measure the body fat percentage. The study conducted the test using 11 subjects, 5 males and 6 females between 15 – 75 years old with the BMI between 16.3 – 33.1 kg/m2. The study used two BIA devices to obtain the body fat percentage results. The subjects experience all four massages and completed the sessions in an hour using the Ogawa MasterDrive 4D. The paired t- test showed that the tvalue is 0.127, and p-value is 0.902. The study is unable to reject the null hypothesis of no difference. Based on the study, the differences of body fat percentage measured by the BIA method is insignificant after using the Ogawa MasterDrive 4D.